IAU Symposium 401: Advancing Reference Systems, Ephemeris, and Standards: from the Earth and the Moon to Solar System Bodies : Book of Abstracts - Fernández, Laura Isabel (2026)
This book compiles all accepted abstracts to the International Astronomical Union (IAU) Symposium 401: Advancing Reference Systems, Ephemeris, and Standards: from the Earth and the Moon to Solar System Bodies (IAUS 401). The IAUS 401 was held in a hybrid format on August 4 to 9, 2025, at the National University of La Plata (UNLP), La Plata, Argentina. It was a joint proposal of IAU Commissions A2: Rotation of the Earth, A3: Fundamental Standards, and X2: Solar System Ephemerides; and the Working Groups Time Metrology Standards and Cartographic Coordinates & Rotational Elements.